2003
DOI: 10.1046/j.1439-0272.2003.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of autogenous leucocytes and Escherichia coli on sperm motility parameters in vitro

Abstract: Urogenital infections are considered important factors in male infertility. In this in vitro study we have evaluated the impact of leucocytes in association with an artificial infection with Escherichia coli on the motility of human spermatozoa. Ejaculates and blood samples were obtained from healthy donors with normal semen parameters. Ejaculates were prepared by swim-up technique and five fractions were isolated for incubation. Leucocyte subtypes were separated from blood samples by gradient centrifugation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 37 publications
1
55
1
1
Order By: Relevance
“…However we found a clear presence of E. Coli and U. Urealyticum in Groups 2 and 3 presenting the worst semen parameters, reduced motility and higher LPO versus Group 1, in which coagulase-negative staphylococci were found more often. The negative effect of E. Coli on sperm motility has already been reported [Diemer et al 2003;Qiang et al 2007]; moreover U. urealyticum phospholipases A and C may influence changes in the lipid composition of the cell membranes of sperm, leading to loss of integrity and increased permeability .…”
Section: Discussionmentioning
confidence: 93%
“…However we found a clear presence of E. Coli and U. Urealyticum in Groups 2 and 3 presenting the worst semen parameters, reduced motility and higher LPO versus Group 1, in which coagulase-negative staphylococci were found more often. The negative effect of E. Coli on sperm motility has already been reported [Diemer et al 2003;Qiang et al 2007]; moreover U. urealyticum phospholipases A and C may influence changes in the lipid composition of the cell membranes of sperm, leading to loss of integrity and increased permeability .…”
Section: Discussionmentioning
confidence: 93%
“…An inhibitory effect of E. coli, serotype 06, on sperm motility has been investigated by some authors (105). Sperm incubated with E. coli demonstrated significant alterations in motility (78,106). Some investigators revealed that the immobilization of spermatozoa may occur as a result of direct contact of the sperm with bacterial cells (105,107).…”
Section: Escherichia Colimentioning
confidence: 99%
“…E. coli probably represents the most frequently isolated microorganism in genitourinary infections (Weidner et al, 1991). E. coli rapidly adheres to human spermatozoa in vitro, resulting in agglutination of spermatozoa (Diemer et al, 2003). Agglutination of spermatozoa was produced only by live pathogenic E. coli whereas killed bacteria failed to do so.…”
Section: Introductionmentioning
confidence: 99%